Herding and the intention to vaccinate against COVID-19 - Gil S. Epstein; Odelia Heizler; Osnat Israeli (Global Labor Organization (GLO), 2025)
This paper investigates the effect of herd behavior, or information cascades, on the willingness to be vaccinated against COVID-19. We use the 2021/2022 wave of the European Social Survey combined with data from the organization Our World in Data and measure the herding behavior as the change in the share of vaccinated people in the population just prior to the individual's decision. Controlling for sociodemographic characteristics, health status, COVID- 19 illness history, and pandemic-related features, the results show that the information cascade significantly increases vaccination intentions. This suggests that the decision on whether to vaccinate is affected by the behavior of others. Moreover, we find a U-shaped association between the herd effect and the share of the population that is vaccinated. Finally, the herd effect on the vaccination decisions of young people, people in poor health, and immigrants is higher than for others.
Keywords: I12; D91; 330; Herd Behavior; COVID-19; Vaccination; European Social Survey; Information Cascades